UNDERSTANDING GUESTS’ HOTEL DESIGN PREFERENCES THROUGH SOCIODEMOGRAPHIC CHARACTERISTICS - Petković, Teodora; Tepavčević, Jelena; Blešić, Ivana (The Business of Tourism, 2025)
Interior design today plays an increasingly important role in the hospitality industry, as it directly affects guests’ impressions, their satisfaction, and their decision to make repeat bookings. Modern hotels are no longer merely places to stay overnight, but spaces that create experiences and evoke emotions. In this context, the style of interior design becomes a key element that defines a hotel’s identity and image. This study examines the differences between modern and classical styles in the design of hotel rooms and lobbies, as well as guests’ preferences for a particular style depending on their sociodemographic characteristics. The research was conducted through an online survey in the Republic of Serbia, including 186 respondents. The results indicate that sociodemographic characteristics largely do not influence preferences for specific styles. Findings show that respondents tend to prefer modern design, while the classical style still holds significant value due to the sense of warmth and comfort it provides. The data suggest that interior design is much more than a visual impression – it is an important tool for creating recognition and guest loyalty. The research results also provide guidance for strategic planning of renovations and investments in interiors, focusing on elements that contribute most to guest satisfaction and positive experiences.
Keywords: interior design; hospitality; design style; aesthetics; guest perception